From agro-waste to bioactive wealth: Analyzing nutraceutical extraction and applications - Alazaiza Motasem, Y. D.; Mokaizh, Aiman Awadh; Baarimah, Abdullah O.; Al-Zghoul, Tharaa M. (Elsevier Ltd, 2025)
The agro and allied sectors generate various wastes, including crop residues, seeds, peels, and husks, which, if not managed properly, can cause significant environmental harm. However, these wastes hold potential as valuable resources that can be transformed into useful components for food, nutraceutical, pharmaceutical, and bioenergy applications. This bibliometric study analyzes research trends, methods, and applications related to agro-waste valorization from 2000 to 2024. The analysis reveals a marked increase in the adoption of green extraction methodologies, such as supercritical fluid extraction and enzymatic extraction, with publications rising from 1 in 2001 to 78 in 2024. Key countries leading this research include India, Brazil, and China, while Portugal is notable for its high average citations per document, indicating impactful research contributions. Prominent journals in this field include “Trends in Food Science and Technology,” “Food Research International,” and “Waste and Biomass Valorization,” which focus on the extraction of bioactive compounds and their applications. The results highlight the potential of agro-waste for developing functional foods, packaging, and other value-added products, while also addressing challenges related to scalability, and variability in bioactive compound recovery. This study underscores the effectiveness of various extraction methods, including supercritical fluid extraction, hydro-methanolic extraction, and solid-state fermentation, in recovering bioactive compounds such as polyphenols, flavonoids, and antioxidants. Future research should focus on optimizing extraction methodologies, enhancing bioavailability, and exploring synergistic approaches to integrate agro-waste processing with renewable energy systems.